How do you simplify # (sqrt3 - sqrt5) (sqrt5 + sqrt7)#?

2 Answers
Aug 14, 2017

Answer:

#sqrt15+sqrt21-5-sqrt35#

Explanation:

Use the foil method:
#(a+b)(c+d)=ac+ad+bc+bd#
#sqrt15+sqrt21-5-sqrt35#

Aug 14, 2017

Answer:

#-5+sqrt(15)+sqrt(21)-sqrt(35)#

Explanation:

you can distribute out the brackets and simplify it
#(sqrt(3)-sqrt(5))(sqrt(5)+sqrt(7))#

#=sqrt(3)*sqrt(5)+sqrt(3)*sqrt(7)-sqrt(5)*sqrt(5)-sqrt(5)sqrt(7)#

because
#sqrt(a)*sqrt(b)=sqrt(ab)#

Our equation becomes
#=sqrt(15)+sqrt(21)-sqrt(25)-sqrt(35)#

#=-5+sqrt(15)+sqrt(21)-sqrt(35)#